Political Reason and the Language of Change Reform and Improvement in Early Modern Europe - Luna-Fabritius, Adriana; Nokkala, Ere; Seppel, Marten; Tribe, Keith (Taylor & Francis, 2023)
FORTHCOMING OPEN ACCESS TITLE This collection of essays re-examines ideas of change and movements for change in early modern Europe without presuming that "progressive" change was the outcome of "reforms". "Reform" today implies rational, incremental change to public institutions and procedures. "Improvement" has a more general application, emphasising the positive outcome to which "reform" is oriented. But the language of reform is today used of historical personalities and movements that did not themselves use the term, and who in many cases were not necessarily seeking the progressive change that we would understand today. The activities of "reform" were embedded in contemporary politics, and while "improvement" was part of a contemporary vocabulary, its real presence has been obscured by the range of natural languages in which it was expressed. Contributors to this volume seek to establish what was meant by contemporary usage. Bringing together scholars of Russia, Southern, Western, Central and Northern Europe, this collection sheds new light on both common and divergent features of a political process too often treated as a uniform movement towards modernity. This volume is a useful resource for students and scholars interested in Enlightenment studies, intellectual history, and conceptual history in early modern Europe.